إدارة الأزمات الاجتماعية في سورة النور حادثة الأفك نموذجا - عرفي، صباح سعيد (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2011)
This research work attempts to study the approach of the Qur'an in crisis management, especially the crisis of slandering against Aishah (Ñazimat al-Ifk) which Qurah al-Nur has discussed in detail. The researcher was the inductive and analytical approaches in order to reach the desired results. One of the important outcomes of this study is to keep people away from the crime of adultery and to block all the pretexts which may lead to it. The study also proves that bad surmising and unverified news may place innocent people in the accusative and suspicious positions. This fact is one of the most important purposes of Qurah al-Nur, as it is very essential to send any information to the subject matter personnel before spreading it so that the hypocrites and sick hearted people may not utilize it against innocent people